2013
DOI: 10.7150/ijms.5182
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Stereological Evaluation of Renal Morphology after Unilateral Ureteral Obstruction

Abstract: Objective and methods: This study established a simple stereological method to obtain quantitative information about two- or three-dimensional structures based on observations from kidney sections in the unilateral ureteral obstruction(UUO) model. Results: Tubulointerstitial area(TA) and TA/the area of a rectangular field(RA) were raised gradually, but significantly, in the obstructed kidney from 1 to 3months post-ligation in comparison to the sham kidney of sham-operated rats(SOR). On the contrary, glomerular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
1
Order By: Relevance
“…40 In addition, our previous study found that the glomerular size gradually enhanced in a time-dependent manner in the contralateral kidneys, which is capable of Exogenous CNP infusion ameliorates UUO-induced TIF P Hu et al compensating for the damaged renal unit of the obstructed kidneys. 20 However, in this study, UUO rats exhibited significant higher BUN and Cr than those in the shamoperation group from 2 weeks to 1 month after ligation; therefore, we believe that systemic inflammation and oxidative stress generated by UUO may mainly contribute to renal damage. 41,42 In this study, in addition to renal protective effects, CNP infusion could also alleviate these above pathological lesions in the obstructed kidneys.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…40 In addition, our previous study found that the glomerular size gradually enhanced in a time-dependent manner in the contralateral kidneys, which is capable of Exogenous CNP infusion ameliorates UUO-induced TIF P Hu et al compensating for the damaged renal unit of the obstructed kidneys. 20 However, in this study, UUO rats exhibited significant higher BUN and Cr than those in the shamoperation group from 2 weeks to 1 month after ligation; therefore, we believe that systemic inflammation and oxidative stress generated by UUO may mainly contribute to renal damage. 41,42 In this study, in addition to renal protective effects, CNP infusion could also alleviate these above pathological lesions in the obstructed kidneys.…”
Section: Discussioncontrasting
confidence: 55%
“…Glomerular volume (GV) was as follows: GV ¼ 4pr max 3 /3 (Figure 1b). 20 Real-Time PCR Total RNA was extracted from renal tissue using TRIzol reagent (Invitrogen, USA). Ultraviolet spectrophotometer measuring absorbance and agarose gel electrophoresis confirmed that there had been no degradation of RNA.…”
Section: Renal Morphologymentioning
confidence: 99%
“…Obstructive nephropathy is one of the most common causes of renal insufficiency in children and adults. Also proportion of patients with known obstructive nephropathy -with or without renal failure-undergoing different surgical procedures under general anesthesia is nonignorable Unilateral ureteral obstruction (UUO) is commonly used model showed to imitate the process of obstructive nephropathy in a feasible, fast and species-independent manner (1,2). Peritubular capillaries rarefaction, tubular atrophy, inflammatory infiltration, widen interstitial space, and progressive tubulointerstitial fibrosis are important morphological features of obstructed kidneys (3,4).…”
Section: Introductionmentioning
confidence: 99%